Węgierski Październik ’56 oczami dziecka. Trzy (warianty) lektury - Warmuz, Daniel (Poznańskie Studia Polonistyczne. Seria Literacka, 2017)
The purpose of this paper is to demonstrate three possible methods of reading and interpreting three consequent literary works on the Hungarian Revolution of 1956 that describe the events from a perspective of an adolescent boy. The mentioned works are the following: The Radiance of Childhood (Gyermekkor tündoklete) by Istvan Kovacs, Hungarian Revolution 1956: Diary (Magyar Forradalom 1956. Naplo) by Gyula Csics and Kalef by Zsolt Berta. The first demonstrated approach provides a documentary-like look on the October 1956 that is given by dint of (auto)biographical elements or diaristic form. The second method ensures much closer analysis of the Hungarian history across time (before, during and after the Revolution) and space (Hungarian country and Budapest). The third approach targets the aspects of initiation into adulthood, masculinity and Hungarian history of the 20th century that allows to read the three stories as a novels of initiation.